Calculating the volume of elongated bubbles and droplets in microchannels from a top view image. Issue 21 (6th March 2015) - Musterd, Michiel; van Steijn, Volkert; Kleijn, Chris R.; Kreutzer, Michiel T.
<x xml:space="preserve">Abstract</x> We present a theoretical model to calculate the volume of bubbles and droplets in segmented microflows from given dimensions of the microchannel and measured lengths of bubbles and droplets.